2009
DOI: 10.1055/s-0029-1208087
|View full text |Cite
|
Sign up to set email alerts
|

Lebensqualität und Behandlungszufriedenheit unter Therapie mit langwirksamen Analoginsulinen

Abstract: There are only a limited number of high quality studies showing that insulin glargine is superior regarding treatment satisfaction and HRQoL of patients with diabetes mellitus. There are fewer publications with good evidence of patient-reported outcomes than those reporting well-established outcomes using HbA1c levels or the incidence of hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…Quality of life is reduced by diabetes-related long-term macro- and microvascular complications such as coronary heart disease comprising angina pectoris, myocardial infarction, congestive heart failure, and nephropathy as well as retinopathy [36]. Different approaches were used in the included studies as shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Quality of life is reduced by diabetes-related long-term macro- and microvascular complications such as coronary heart disease comprising angina pectoris, myocardial infarction, congestive heart failure, and nephropathy as well as retinopathy [36]. Different approaches were used in the included studies as shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin glargine [25, 26] (Lantus) (Figure 2) is the first long-acting insulin analogue having amino acid modifications in both chains. In the A-chain, the asparagine at position 21 is substituted by glycine and the B-chain is elongated at the C-terminus by addition of two arginine residues.…”
Section: Long-acting Basal Insulin Analoguesmentioning
confidence: 99%
“…Insulin detemir [25, 27] (Levemir) (Figure 2) is characterized by acylation of myristic acid to the lysine residue at position 29 in the B-chain and deletion of the last threonine (position 30) in the B-chain. Its protracted action is achieved through delayed resorption caused by the increased self-association and reversible albumin binding at the injection site as well as because albumin binding causes buffering of insulin concentration.…”
Section: Long-acting Basal Insulin Analoguesmentioning
confidence: 99%
“…Die diskutierten Studien lassen schlussfolgern, dass einfache Therapieschemata bezüglich einer guten Stoffwechselkontrolle effektiv sind und positive Effekte auf die Lebensqualität aufweisen. Insbesondere im Hinblick auf eine Reduktion des Hypoglykämie-risikos sowie einer Verbesserung der Behandlungszufriedenheit und der Lebensqualität älterer Menschen wäre ein einfaches Therapieschema auch im hohen Lebensalter wünschenswert[20][21][22]25]. Bei der hier vorliegenden Untersuchung handelt es sich um eine Erhebung von Primärdaten in einem schwer zugänglichen Bereich des Gesundheitswesens.…”
unclassified